A UK survey of COVID‐19 related social support closures and their effects on older people, people with dementia, and carers. (25th September 2020) - Giebel, Clarissa; Lord, Kathryn; Cooper, Claudia; Shenton, Justine; Cannon, Jacqueline; Pulford, Daniel; Shaw, Lisa; Gaughan, Anna; Tetlow, Hilary; Butchard, Sarah; Limbert, Stan; Callaghan, Steve; et al.
Abstract: Objectives: The aim of this national survey was to explore the impact of COVID‐19 public health measures on access to social support services and the effects of closures of services on the mental well‐being of older people and those affected by dementia. Methods: A UK‐wide online and telephone survey was conducted with older adults, people with dementia, and carers between April and May 2020. The survey captured demographic and postcode data, social support service usage before and after COVID‐19 public health measures, current quality of life, depression, and anxiety. Multiple linear regression analysis was used to explore the relationship between social support service variations and anxiety and well‐being. Results: Five hundred and sixty‐nine participants completed the survey (61 people with dementia, 285 unpaid carers, and 223 older adults). Paired samples t ‐tests and X 2 ‐tests showed that the mean hour of weekly social support service usage and the number of people having accessed various services was significantly reduced post COVID‐19. Multiple regression analyses showed that higher variations in social support service hours significantly predicted increased levels of anxiety in people with dementia and older adults, and lower levels of mental well‐being in unpaid carers and older adults. Conclusions: Being unable to access social support services due to COVID contributed to worse quality of life and anxiety in those affected by dementia and older adults across the UK. Social support services need to be enabled to continue providing support in adapted formats, especially in light of continued public health restrictions for the foreseeable future.